The Influence of Transparency and Social Accountability on Village Fund Management in Gorontalo Regency Perspective of Sharia Financial Management - Yusuf, Sri Dewi; Ajuna, Luqmanul Hakim; Ardi, Muhamad; Mohamad, Roni (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2023)
The aim of this study is to find out and evaluate the transparency and accountability of village fund management on the level of community welfare in Gorontalo Regency from the perspective of Sharia financial management. This is a quantitative study that employs quantitative data as primary data from 129 village fund managers in Gorontalo regency. SEMP-PLS is used to analyze the data. The findings revealed that: (1) Accountability positively and significantly influences the level of community welfare; (2) Transparency positively and significantly influences the level of community welfare; (3) Transparency positively and significantly influences the management of village funds; (4) Accountability negatively but insignificantly influences the management of village funds; (5) Village fund management positively and significantly influences the level of community welfare; (6) Transparency, which is mediated by village fund management, has a favorable and considerable impact on the community's welfare level; (7) Accountability through village fund management has a detrimental but non-significant influence on community wellbeing; (8) According to the findings, village fund management has yet to consider the values of Sharia financial management. Penelitian ini bertujuan untuk menganalisis pengaruh transparansi dan akuntabilitas pengelolaan dana desa terhadap tingkat kesejahteraan masyarakat di Kabupaten Gorontalo perspektif manajemen keuangan Syariah. Penelitian ini merupakan penelitian kuantitatif menggunakan data primer dengan jumlah sampel 129 responden di ambil dari pengelola dana desa di Kabupaten Gorontalo. Analisis data yang digunakan adalah metode SEM-PLS Hasil penelitian menunjukan bahwa: (1) Transparansi berpengaruh positif tetapi tidak signifikan terhadap tingkat kesejahteraan masyarakat; (2) Akuntabilitas berpengaruh positif dan signifikan terhadap tingkat kesejahteraan masyarakat; (3) Transparansi berpengaruh positif dan signifikan terhadap pengelolaan dana desa; (4) Akuntabilitas berpengaruh negatif tetapi tidak signifikan terhadap pengelolaan dana desa; (5) Pengelolaan dana desa berpengaruh positif dan signifikan terhadap tingkat kesejahteraan masyarakat; (6) Transparansi yang dimediasi oleh pengelolaan dana desa berpengaruh positif dan signifikan terhadap tingkat kesejahteraan masyarakat; (7) Akuntabilitas yang dimediasi oleh pengelolaan dana desa berpengaruh negatif tetapi tidak signifikan terhadap tingkat kesejahteraan masyarakat; (8) Hasil penelitian juga menunjukan bahwa dalam pengelolaan dana desa belum mencerminkan nilai-nilai pengelolaan keuangan Syariah.